Level of Coherence in L2 Written Text: A Gender Perspective - Fairooz, Rashad Ahmed (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Writing is an essential skill for EFL learners to be able to communicate effectively. Achieving effective communication is condemned by the degree of developing text coherence. Reviewing the related literature shows that coherence, unlike other text features, posits a significant problem with L2 learners, males and females. Due to biological and cultural differences between males and females, both sexes may bring variety to coherence development in text writing. This case has not received a due account in discourse analysis studies, creating a gap in the literature. Accordingly, the present study aimed to identify the level of coherence in L2 written texts from a gender perspective. To achieve the objectives of the study, all 40 graduates of English, 20 males, and 20 females, Faculty of Education, Ibb University, Yemen, in the academic year 2019 – 2020, participated in this study. A writing test was used as a research tool to collect the required data. Using both descriptive and inferential research approaches, a number of findings were revealed. The most important ones are: there was a lack of coherence in both males' and females' written texts (M = 15.45/30, SD = 4.56); and there were no statistically significant differences between the mean score of male and female graduates (M = 16.10 > 14.80 <, SD = 4.96 > 4.14 , t = - 0.90, P > 0.05) attributed to the variable of gender. Based on the findings of the study, a number of pedagogical implications were introduced; most notably, policymakers, course designers, and teachers should pay ample attention to the contents of writing courses focusing on text coherence to sensitize EFL learners to such a text feature to be able to produce coherent texts.